Searching new structures of beryllium-doped in small-sized magnesium clusters Be2 Mgn Q (Q = 0, -1; n = 1-11) clusters DFT study - Zeng, Lu (Journal of computational chemistry, 2020)
© 2020 Wiley Periodicals LLC.